One Step Closer to Understanding Motivation in Scientific Education: The Incorporation of Science Textbooks as a Predictor, Together with Motivational Climate and Basic Psychological Needs (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
Students’ increasing lack of interest in science has led to a disturbing situation that compels us to continue researching educational motivation, in this line, and within the framework provided by self-determination and achievement goal theories. The great importance of this variable can be attributed to its relevance in classes and its competence-related nature, which in principle makes it a motivating resource, as is the case with science textbooks. In particular, this study provides an in-depth understanding of motivation using various motivational predictors, while incorporating the motivational competence relevance of science books. One thousand students between the ages of 10 and 14 years participated. The research instrument used was a questionnaire consisting of 4 scales that measured the motivational competence relevance of science books, the task-oriented motivational climate, the basic psychological need for competence and the intrinsic motivation. Data were analyzed using correlation analysis and a structural equations model. The results showed that, among other aspects, motivation is influenced by competence, while competence is influenced by the task climate and the motivational competence relevance of science books. These findings suggest that in order to increase students’ intrinsic motivation, teachers must create a task-oriented climate, emphasize the value that student should attribute to science books from a motivational competence perspective, and satisfy the need for competence.